A Multi-Theoretical and Multi-Method Family Study Approach to Preschool Inhibitory Control: Links to Working Memory, Receptive Vocabulary, Behavioral Maladjustment, and Parent Mental Health in the Context of Temperament and Executive Functioning Perspectives - Gagne, Jeffrey R.; Barker, Kaelyn; Chang, Chi-Ning; Nwadinobi, Ogechi K.; Kwok, Oi-Man (Frontiers in Psychology, 2021)
Inhibitory control (IC) is defined as the executive functioning (EF) and self-regulatory temperamental inhibition of impulsive or pre-potent behavior consistently associated with multiple cognitive and socio-emotional difficulties including academic and learning challenges, externalizing behavior problems and attention deficit hyperactivity disorder (ADHD) in childhood. Investigations including both theoretical perspectives on IC--the temperament and the EF approaches, are of considerable interest and will best inform future education, prevention and intervention efforts. This investigation examined child IC, working memory (WM), vocabulary, behavior problems, and maternal depression and anxiety employing a family study design. Participants included 99 families with two typically developing preschool children (N=198) and one parent. Child IC was assessed using a parent-rating scale, three observer ratings, two laboratory temperament episodes, and an EF Stroop task. Child WM and vocabulary were measured using standard assessment techniques, and remaining measures were parent-reported. Most IC measures were correlated in the expected directions, and with WM and vocabulary. All IC variables, WM and vocabulary were significantly related to externalizing behavior problems. Lower parent-rated IC, and higher levels of externalizing behavior problems were positively associated with maternal depression and anxiety (lower vocabulary level was related to depression). The results of our hypothesized Structural Equation Modeling (SEM) model showed that the IC Temperament factor, composed of the six temperament IC measures, had a positive effect on vocabulary, while the IC-Stroop positively predicted WM (the model supported several of the correlational findings). Overall, the IC Temperament factor and other covariates together accounted for 22.5% of the variance in vocabulary, whereas IC-Stroop and other controlled variables could explain 49.8% of the variance in WM. These findings indicate that theoretical perspectives (in this case temperament and EF IC contexts) and assessment methods are an important consideration when interpreting the results of early IC investigations. Although most assessments of IC were associated with the outcomes under study, we found specific associations between temperament measures of IC and vocabulary as well as externalizing, and IC-Stroop and WM. Future studies will employ this assessment approach in preschool to predict temperament, EF, and behavioral and academic adjustment in elementary school longitudinally.